Implementasi Model Pembelajaran Problem Based Learning Berbantuan Permainan Ular Tangga untuk Meningkatkan Kemampuan Pemecahan Masalah Matematis Siswa - Resnika; Asep Sahrudin; Ika Yunitasari (Tumoutou Social Science Journal, 2026)
This study aims to determine whether the Problem Based Learning (PBL) model assisted by a snakes and ladders game can improve students' mathematical problem-solving abilities. The study was conducted using a quantitative model through the following stages: formulating the problem, literature review, hypothesis submission, determining the method, preparing research instruments, collecting and analyzing data, and drawing conclusions. Based on the results of the hypothesis analysis test of mathematical problem-solving ability using an independent t-test, the sig. (2-tailed) value was 0.000 < 0.05, so it can be concluded that the Problem Based Learning model assisted by a snakes and ladders game can improve students' mathematical problem-solving abilities. The result of the average N-Gain of mathematical problem-solving ability was 0.7299, indicating that the Problem Based Learning class had a high level of improvement. So it can be used as an alternative model in mathematics learning at the vocational high school level on probability material.